PENGEMBANGAN E-BOOK BERBASIS ANDROID UNTUK MENINGKATKAN ANTUSIASME BELAJAR SISWA (Studi Pada Mata Pelajaran Fisika Kelas XI IPA SMA Kota Bengkulu) - Rice Wira Gustian; Riyanto Riyanto (DIADIK, 2020)
Thepurpose of thisstudytoproduceane-bookapplicationbasedonandroidinphysics learning,totestthe effectivenessof e-booksdeveloped in increasingstudententhusiasm forlearning physics,and todescribe theeffectivenessofe-bookwhichwascomparedby learningresources.The subjectsofthisstudywereteachersandhighschoolstudents,in thelimitedscaletestthe subjectswereSMAN6,andinthebroadscaletestthesubjects were SMAN3,SMAN2and SMAN8.Theobjectofthisstudy isane-bookapplication basedonandroidfor physicssubjectsinXI ScienceClasswhichwasdevelopedbythe Sigil1.2.0application.Theresultsof thisstudyinthe e-bookfeasibilitytestobtainedan averagevalueof89fromteacherrespondentsand85fromstudentrespondentsmeant thatthedevelopede-bookwasworthyofbeingasourceoflearning, whileforthe enthusiasmquestionnaireobtainedanaverageof78.33fortheexperimentalclassand 71.33forthecontrolclassshows thattheuseofan e-bookapplicationbasedandroidasa learning resource canincreasestudententhusiasmforlearningphysics